Space and planning in secondary cities Reflections from South Africa - Marais, Lochner; Nel, Verna (UJ Press, 2019)
Much of the urban research focuses on the large metropolitan areas in South Africa. This book assesses spatial planning in the second-tier cities of the country. Secondary cities are vital as they perform essential regional, and in some cases, global economic roles and help to distribute the population of a country more evenly across its surface. Apartheid planning left South African cities fragmented segregated and with low densities. Post-apartheid policies aim to reverse these realities by emphasising integration, higher densities and upgrading. Achieving these aims has been challenging and often the historical patterns continue. The evidence shows that two opposing patterns prevail, namely increased densities and continued urban sprawl. This book presents ten case studies of spatial planning and spatial transformation in secondary cities of South Africa. The book frames these case studies against complexity theory and suggests that the post-apartheid response to apartheid planning represents a linear deviation from history. The ten case studies then reveal how difficult it is for local decision-makers to find appropriate responses and how current responses often result in contradictory results. Often these cities are highly vulnerable and they find it difficult to plan in the context of uncertainty. The book also highlights how these cities find it difficult to stand on their own against the influence of interest groups (property developers, mining companies, traditional authorities, other spheres of government). The main reasons include weak municipal finance statements, the dependence on national and provincial government for capital expenditure, limited investment in infrastructure maintenance, the lack of planning capacity, the inability to implement plans and the unintended and sometimes contrary outcomes of post-apartheid planning policies.